2020
DOI: 10.3389/fmicb.2020.00079
|View full text |Cite
|
Sign up to set email alerts
|

Extremophilic Natrinema versiforme Against Pseudomonas aeruginosa Quorum Sensing and Biofilm

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen that causes high morbidity and mortality rates due to its biofilm form. Biofilm formation is regulated via quorum sensing (QS) mechanism and provides up to 1000 times more resistance against conventional antibiotics. QS related genes are expressed according to bacterial population density via signal molecules. QS inhibitors (QSIs) from natural sources are widely studied evaluating various extracts from extreme environments. It is suggested that extremely halo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The majority of these QQ molecules have been isolated from natural sources (LaSarre and Federle, 2013). The result of a recent study revealed QS inhibitory potentials of ethyl acetate extracts from cell-free supernatants and cells of Natrinemaversi forme against P. aeruginosa biofilm (Başaran et al, 2020). Many QS inhibitors from plant-based natural products have been identified (Caceres et al, 2020;Zhong et al, 2020) and proposed to be effective in future biofilm targeting strategies.…”
Section: Quorum Sensing Targeting Strategiesmentioning
confidence: 99%
“…The majority of these QQ molecules have been isolated from natural sources (LaSarre and Federle, 2013). The result of a recent study revealed QS inhibitory potentials of ethyl acetate extracts from cell-free supernatants and cells of Natrinemaversi forme against P. aeruginosa biofilm (Başaran et al, 2020). Many QS inhibitors from plant-based natural products have been identified (Caceres et al, 2020;Zhong et al, 2020) and proposed to be effective in future biofilm targeting strategies.…”
Section: Quorum Sensing Targeting Strategiesmentioning
confidence: 99%
“…The Group 2 coating shown a circular hydroxyapatite shape with 4-6 µm diameter. Clearly, the nanoscale surface has strong antimicrobial efficacy by inhibiting the S epidermidis growth 46,[48][49][50][51][52][53] . In previous studies, it was investigated the behavior of gram positive and negative bacteria on TiO 2 nanotubes.…”
Section: Resultsmentioning
confidence: 99%
“…Biofilm development, mainly in the sessile growth phase, is regulated by intracellular QS interaction [37]. This happens also in different pathogens, including, for example, Pseudomonas aeruginosa, which can colonize and then be transmitted also by food, establishing opportunistic infections with high mortality rates [38]. The potential role of QS in spoilage has recently attracted growing research interest.…”
Section: Quorum Sensing In Agriculture and Foodmentioning
confidence: 99%
“…The above-described strategies to counteract the food crisis in an eco-friendly manner are summarized in Table 1. [ [34][35][36][37][38][39][40][41] Moreover, standard laboratory settings are ideal and highly controlled, but cannot extensively represent realistic environments, in which chemical and physical conditions dynamically change. Consequently, further efforts are needed in the study of QS in microbial mixtures of species that mimic real habitat parameters [42].…”
Section: Quorum Sensing In Agriculture and Foodmentioning
confidence: 99%